THE ROLE OF LOCAL GOVERNMENT ON FACING TSUNAMI DISASTER IN PACITAN, EAST JAVA - Ratih Probosiwi (Pusbindiklat - LIPI, 2015)
In disaster risk management, government plays important role as decision maker on disaster risk reduction policies. The capability of local governments to manage disaster risk starting from the early stages before the disaster occurs until disaster occurs by reconstruction plans. Pacitan government has an important responsibility considering Pacitan coastal is prone to tsunami. Through structured interviews and focus group discussion (FGD) to the authorities agencies, the study found that the government has tried to reduce the risk of a tsunami through the emergency policy, early warning systems, and resource mobilization. Although historically, Pacitan tsunami had never experienced tsunami directly, but the local government has done a good preparation in the face of the tsunami in terms of both physical and non-physical efforts.